Probiotic Supplementation Facilitates Recovery of 6-OHDA-Induced Motor Deficit via Improving Mitochondrial Function and Energy Metabolism - Nurrahma, Bira Arumndari; Tsao, Shu-Ping; Wu, Chieh-Hsi; Yeh, Tu-Hsueh; Hsieh, Pei-Shan; Panunggal, Binar; Huang, Hui-Yu (Frontiers in Aging Neuroscience, 2021)
Parkinson’s disease (PD) is a neurodegenerative disease associated with progressive impairment of motor and non-motor functions in aging people. Overwhelming evidence indicate that mitochondrial dysfunction is a central factor in PD pathophysiology, which impairs energy metabolism. While, several other studies have shown probiotic supplementations to improve host energy metabolism, alleviate the disease progression, prevent gut microbiota dysbiosis and alter commensal bacterial metabolites. But, whether probiotic and/or prebiotic supplementation can affect energy metabolism and cause the impediment of PD progression remains poorly characterized. Therefore, we investigated 8-weeks supplementation effects of probiotic [Lactobacillus salivarius subsp. salicinius AP-32 (AP-32)], residual medium (RM) obtained from the AP-32 culture medium, and combination of AP-32 and RM (A-RM) on 6-hydroxydopamine (6-OHDA)-induced PD rats. We found that AP-32, RM and A-RM supplementation induced neuroprotective effects on dopaminergic neurons along with improved motor functions in PD rats. These effects were accompanied by significant increases in mitochondrial activities in the brain and muscle, antioxidative enzymes level in serum, and altered SCFAs profile in fecal samples. Importantly, the AP-32 supplement restored muscle mass along with improved motor function in PD rats, and produced the best results among the supplements. Our results demonstrate that probiotic AP-32 and A-RM supplementations can recover energy metabolism via increasing SCFAs producing and mitochondria function. This restoring of mitochondrial function in the brain and muscles with improved energy metabolism might additionally be potentiated by ROS suppression by the elevated generation of antioxidants, and which finally leads to facilitated recovery of 6-OHDA-induced motor deficit. Taken together, this work demonstrates that probiotic AP-32 supplementation could be a potential candidate for alternate treatment strategy to avert PD progression.